Efects of silver nitrate on in vitro development of yam (Dioscorea rotundata Poir) plants - Oluwasegun, R.Y.; Uchendu, E.E.; Adeyemi, A.; Abberton, M. (2025)
Yam (Dioscorea spp.) production is constrained by many factors including insufficient planting materials, diseases, and climate change. Plant tissue culture (PTC) offers practical solutions for rapid propagation of many plant types. However, ethylene buildup during PTC is a major challenge to in vitro plant growth and development. This study examined the effects of silver nitrate (AgNO3), a known ethylene action blocker on the in vitro growth and development of four accessions of D. rotundata in a 7*6*4 factorial outline in a completely randomized design. Nodal explants (700) of four accessions (TDr 3134, TDr 2745, TDr 3291, and TDr 2859) were transferred to culture media containing Murashige and Skoog basal salts with vitamins including different concentrations of AgNO3 (0 to 6.0 mg L−1). The numbers of leaves, shoots, and roots, plant heights, and length of roots per explant were recorded weekly until week 6. After the 6th week, 420 in vitro plantlets with well-established roots were selected for acclimatization. The responses of the yam plants to AgNO3 were genotype dependent, with specific optimal concentration for different plant parts. Addition of 1.0 mg L−1 AgNO3 to the culture medium significantly improved in vitro growth and development of the shoots, while 2.0 mg L−1 AgNO3 significantly influenced root formation. There were no negative residual effects of AgNO3 on the D. rotundata plantlets as more than 85% of the accessions survived during acclimatization, with good plant vigor. This study demonstrates the effectiveness of silver nitrate (AgNO3) in enhancing the morphogenesis of D. rotundata.